Scenario of Municipal Waste Management in Malaysia - Liew, Zachary Raphael; Monir, Minhaj Uddin; Kristanti, Risky Ayu (Tecno Scientifica Publishing, 2021)
Malaysia has rapidly modernized, with most of the population now residing in cities and the remainder in rural or remote areas. The amount of municipal solid waste generated has increased in tandem with the country's rapid urbanization in response to that statement. Due to a lack of connectivity in rural areas, there may be insufficient infrastructure for a proper waste management system. As a result, illegal waste dumping was common, and landfills' massive volumes of waste may contribute to greenhouse gas emissions. The Malaysian government has responded by taking the necessary steps to upgrade the country's current waste management system in order to better manage municipal solid waste disposal. This research looks at how energy recovery from accumulated waste can be used as a renewable energy source, as well as the current issues, challenges, and proposed solutions. Methane gas produced as a byproduct of waste decomposition in landfills or disposal sites was used to generate electricity more efficiently and sustainably, resulting in a positive economic and environmental outcome.